Cost-Effectiveness of Pre-exposure Prophylaxis Among Men Who Have Sex With Men in China: A Systematic Review - Mi, Yuanqi; Zeng, Yuhong; Wang, Peicheng; Zhou, Mengge; Cheng, Feng (Frontiers in Public Health, 2022)
Objective: Men who have sex with men in China meet the definition of the population at "substantial risk" of getting human immunodeficiency virus by the World Health Organization, therefore initiating pre-exposure prophylaxis was recommended in this population. Lack of convincing evidence of cost-effectiveness results in the unavailability of large-scale PrEP implementation at a national level. The objective of this review is to assess the cost-effectiveness of pre-exposure prophylaxis implementation among men who have sex with men in China. Methods: The following database were used to search studies of pre-exposure prophylaxis in China in English and Chinese language: PubMed, Embase, CNKI (China National Knowledge Infrastructure), and Wanfang Database. Inclusion criteria included: pre-exposure intervention, year for publication (2007-2021), setting (China), and cost-effectiveness estimation. Results: Seven studies were identified. We found that pre-exposure prophylaxis is only cost-effective among regular men who have sex with men with a reduction of the current market price. Pre-exposure prophylaxis is potentially cost-effective when combined with other preventive programs or delivered to the population with a high risk of human immunodeficiency virus exposure. Conclusion: Our study identifies key considerations in cost-effectiveness evaluation– cost assumptions, implementation coverage, and targeted population. The scarce evidence available is not comparable to some extent; thus, inadequate for decision making. Consequently, it calls for more standard and transparent modeling studies. Keywords: human immunodeficiency virus; China; pre-exposure prophylaxis; men who have sex with men; homosexual; cost-effectiveness.